Urban livelihood - Schmidt, Carl (School of Architecture, Planning and Geomatics, 2024)
Problem statement The CBD of Cape Town is found within the walled-in mountainous valley, commonly referred to as the City Bowl. Market forces are pushing small-scale businesses/craftsperson's from this economically vibrant area with very few affordable retail / workspace opportunities on offer. The residential component of the CBD has a similar set of problems with market forces. There are too few housing opportunities for the middle- and lower-income groups. Market forces perpetuate the narrative of developing housing opportunities for these income groups on the periphery of the metropole, far from economic activity. The Research Question How can underutilised state-owned properties along a key movement route in the Cape Town City Bowl be reimagined to promote economic diversity and inclusion? Proposed Goal Titled “Urban Livelihoods”, this project sets out to reimagine the economic centre of Cape Town, with inclusive, well-located housing and economic opportunities. Proposed Solution This project explores how we can stitch new designs into the existing fabric of the City Bowl of Cape Town, using well-located parcels of land and available buildings. Key well located state-owned sites are identified within economically vibrant neighbourhoods. These sites will be reimagined to envisage inclusive residential and economic opportunities within the CBD of Cape Town. Methods The researcher gathered information from interviews, site visit observations, mapping and sketching the CBD. This information was curated and formed the basis for the designs that followed. Design Conclusion The creative element of this project inspires an urban design framework to reinvigorate stagnant land or buildings and strategies to harness the productive energies of a city. Through these mechanisms, vibrant spaces will open and foster thriving communities. If these frameworks and strategies can be achieved, maintained, and yield inclusive growth then the project is a success